Characterization of Ta–W alloy films deposited by molten salt Multi-Anode Reactive alloy Coating (MARC) method. (November 2015) - Lee, Young-Jun; Lee, Tae-Hyuk; Nersisyan, Hayk H.; Lee, Kap-Ho; Jeong, Seong-Uk; Kang, Kyoung-Soo; Bae, Ki-Kwang; Park, Kyoung-Tae; Lee, Jong-Hyeon
Abstract: The harsh atmosphere of the sulfur–iodine process used for producing hydrogen requires better corrosion resistance and mechanical properties than are possible to obtain with pure tantalum. Ta–W alloy is superior to pure tantalum but is difficult to alloy due to its high melting temperature. In this study, substrate samples were coated with Ta–W (Ta–7W, Ta–4W and Ta–1W) using the Multi-Anode Reactive alloy Coating (MARC) process in molten salt (LiF–NaF–K2 TaF7 ), with varying distances between cathode and anode. In the case of Ta–4W, a corrosion rate of less than 0.011 mm/year was attained in hydriodic acid at 160 °C, and thickness uniformity was 80.3 ± 2.15 μm. Also, the resulting coated films had hardnesses up to 12.9% stronger than pure tantalum coated film. The alloy coating films also contributed to significant enhancement of corrosion resistance. Graphical abstract: Highlights: Ta–W alloy was coated onto a SUS substrate by molten salt MARC method. Ta–W alloy layer related to the microstructural changes associated with W contents. Microstructure of Ta–W alloy coating layer was investigated by OIM and FE-SEM. Ta–4.36W alloy layer showed 0.011 mm/year corrosion rate in hot conc. HI acid.